KUALITAS PELAYANAN PRAMUSAJI PADA MASA PANDEMI COVID 19 DI RESTAURANT ALL DAY DINNING NOVOTEL HOTEL PEKANBARU - Fika Mauli Dina; Andri Sulistyani (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
This research is entitled Quality of Waiters Service During the Covid-19 Pandemic at the Novotel Hotel Restaurant Pekanbaru. This study aims to determine the Quality of Waiters Service During the Covid-19 Pandemic at the Novotel Hotel Restaurant Pekanbaru, In addition, this study also aims to determine the form of restaurant service at the Novotel Hotel. This research is a quantitative research using a descriptive approach that describes and explains the situation that occurs by collecting data and information in the field. The samples used in this study were 100 people. This research was conducted at the Novotel Hotel Pekanbaru restaurant. The research was carried out for 4 months, starting from January - April 2021. The key informants in this study were 1 Food and Beverage Manager Novotel Pekanbaru. Data collection techniques using observation techniques, questionnaires, interviews and documentation. Based on the results of the study, it can be said that the Quality of Waiters Service During the Covid-19 Pandemic at the Novotel Pekanbaru Restaurant was good in all respects which refers to the grand theory of service quality which includes Tangibles (Physical Evidence), Realibility (Reliability), Responsieveness (responsiveness), Assurance (Assurance) and Empathy. This is evidenced by the results of scores from visitors who have visited the Novotel Pekanbaru restaurant in 2021 with good scores. Keywords: Service Quality, Waiters, Restaurant, Guests